MENGULIK FUNDAMENTAL SAHAM PERBANKAN SYARIAH - Atikah, Siti; Waskito, Iman (Jurnal Riset Akuntansi, 2025)
This study investigates the financial performance and market valuation of four Islamic Commercial Banks (Bank Umum Syariah/BUS) listed on the Indonesia Stock Exchange over the period 2019–2024. A descriptive approach is applied to secondary data compiled from published financial statements and market information, which are then interpreted with signaling theory and firm value perspectives. The results show that BUS1 experiences the most comprehensive improvement: profitability rises, efficiency and financing quality improve, liquidity and capital structure remain sound, and this is followed by sustained EPS growth. BUS2 maintains powerful fundamentals—high ROA, ROE, EPS, low NPF, prudent FDR, and robust CAR—yet its PBV and PER decline sharply, indicating a downward adjustment of market premium despite solid performance. BUS3 and BUS4 record volatile profitability, high operating costs and leverage, and more risky FDR patterns, so that their PBV remains low or highly unstable and PER often negative values, signalling persistent market scepticism and speculative pricing. Overall, the evidence supports the view that, in Indonesian Islamic banking, a combination of strong profitability, efficiency, asset quality, funding structure, and capital adequacy is consistently rewarded by better stock valuation, in line with signaling theory.